Determination of the morphological pattern of pacu’s (Piaractus mesopotamicus) gills - Alves, Luiz Fernando de Souza; Saravy, Taiany Miranda; Baldo, Grace Alessandra Araújo; Gabriel, Andrea Maria de Araújo; Cavichiolo, Fabiana (Scientia Agraria Paranaensis, 2017)
In order to carry out pathological evaluations or recognition of changes in the morphology of pacu gills, it is necessary to know a regular morphological pattern, which is the purpose of this study. Twenty animals (Piaractus mesopotamicus) were collected from cultivated environments of the “Grande Dourados” region, Mato Grosso do Sul State, Brazil, with an average total length of 35 cm and 750 g. During collection, the animals were anesthetized with benzocaine, euthanized and dissected for macroscopic evaluation of the organs “in situ”. The gills were fixed in Bouin's solution and stained by the usual Hematoxylin/Eosin method and the alcian blue + PAS technique (Schiff periodic acid). Macroscopically it was observed that the gills were bright red, internally located, protected by the opercula, with numerous spaced traces, filaments and secondary lamellae. Under the light microscopy it was possible to identify the gill’s arteries, cartilaginous structure, pillar cells, respiratory epithelium and mucous cells. We conclude that this species has a gill structure very similar to that of other freshwater teleosts, but more studies are necessary to compare this structure in all phases of its life and different times of the year.